Do Subway Openings Reduce Air Pollution? A Replication Exercise - Michael Wiebe (Institute for Replication (I4R), 2024)
Gendron-Carrier et al. (2022) studies the effect of subway openings on urban air pollution. The authors find a null average effect, but a negative effect in cities with high initial pollution. In this comment, I perform several robustness checks on the negative effect for high-pollution cities, and repeat the main analyses for low-pollution cities. I show that the main finding for high-pollution cities is robust, and find mixed results for low-pollution cities. I implement an alternative back-of-the-envelope calculation for the effect of subway openings on infant mortality, and find a smaller number of averted deaths.
Keywords: 330